2016
DOI: 10.1155/2016/9797021
|View full text |Cite
|
Sign up to set email alerts
|

Significant Contribution of Mouse Mast Cell Protease 4 in Early Phases of Experimental Autoimmune Encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a mouse model that reproduces cardinal signs of clinical, histopathological, and immunological features found in Multiple Sclerosis (MS). Mast cells are suggested to be involved in the main inflammatory phases occurring during EAE development, possibly by secreting several autacoids and proteases. Among the latter, the chymase mouse mast cell protease 4 (mMCP-4) can contribute to the inflammatory response by producing endothelin-1 (ET-1). The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
(43 reference statements)
4
12
0
Order By: Relevance
“…19 MCPT5 has elastase-like proteolytic activity, 20 and MCPT4, similar to human chymase, has chymotryptic activity. 21 Although MCPT4 aggravates disease in models of arthritis, 22 abdominal aortic aneurysm, 23 autoimmune encephalitis, 24 and renal diseases, 25,26 it also neutralizes toxins 27 and improves allergic inflammation, 28 posttraumatic brain inflammation, 29 and kidney fibrosis. 30 In IRI, MCs become activated locally and systemically, [31][32][33] causing damage in the brain, 32 intestine, [34][35][36] heart, 37 and skeletal muscle.…”
mentioning
confidence: 99%
“…19 MCPT5 has elastase-like proteolytic activity, 20 and MCPT4, similar to human chymase, has chymotryptic activity. 21 Although MCPT4 aggravates disease in models of arthritis, 22 abdominal aortic aneurysm, 23 autoimmune encephalitis, 24 and renal diseases, 25,26 it also neutralizes toxins 27 and improves allergic inflammation, 28 posttraumatic brain inflammation, 29 and kidney fibrosis. 30 In IRI, MCs become activated locally and systemically, [31][32][33] causing damage in the brain, 32 intestine, [34][35][36] heart, 37 and skeletal muscle.…”
mentioning
confidence: 99%
“…C57Bl/6 mice genitors were purchased from Charles River Canada (Montréal, QC, Canada) and mMCP-4 knockout (KO) mice genitors were provided by Dr. Gunnar Pejler (Uppsala University, Sweden) and were bred in our facility. The mMCP-4 KO mice were backcrossed for over 10 generations with C57Bl/6 congeners; therefore, they are highly congenial with the later strain (Tchougounova et al, 2003) as previously reported (Desbiens et al, 2016). We and others had also previously reported the complete loss of chymasedependent hydrolytic activity in mMCP-4 KO mice in vivo as well as in tissues or MCs derived from this mouse strain (Hendrix et al, 2013;Houde et al, 2013;Semaan et al, 2015).…”
Section: Methodsmentioning
confidence: 87%
“…mMCP-4 is also involved in early neuromotor disabilities associated with EAE (Desbiens et al, 2016). We have previously shown that genetic repression of mMCP-4 improved clinical signs and reduced spinal cord damage afforded by EAE in the mouse model (Desbiens et al, 2016). Furthermore, EAE triggers a significant increase in mMCP-4 mRNA levels in the CNS as well as production of cerebral immunoreactive ET-1.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it should be kept in mind that Mcpt5 has no known functional homologue in humans (see “Chymases and chymase knockouts”), and the bearing of this finding on human arthritis is thus not clear. Chymase has also been reported to contribute to the pathology of experimental autoimmune encephalomyelitis, a model for autoimmune multiple sclerosis [80].…”
Section: Chymase In Autoimmune Settingsmentioning
confidence: 99%